Analisis Strategi Bersaing Bisnis Produsen Kereta Mainan dengan Pendekatan SWOT pada CV. XYZ - Darmansyah, Mochammad Rico; Muttaqin, Aan Zainal; Susanto, Doni (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
One phenomenon that often occurs in residential areas is the night market. Night markets offer lively and affordable entertainment for the community with various game rides such as carousels, Ferris wheels, and mini trains. The existence of various night market toys is certainly inseparable from the existence of manufacturing industries that produce night market toys and mini trains. One of the fairly large ones in Madiun is CV. XYZ, which is engaged in the manufacture, trade, services, supply, and sale of various kinds of mini trains and children's toys. Every industry certainly faces competition, so CV. XYZ is no different, so analysis is needed to determine the company's competitive position and the strategies needed to remain competitive with its competitors. SWOT analysis and the CPM matrix can be used so that companies can determine the right strategy in business competition and determine the company's competitive position. From the data that has been processed using the SWOT matrix, IE matrix, and CPM matrix, the results obtained are (-0,14 ; 0,375), which is in quadrant II supporting the Diversification strategy.